Functional connectivity of the hippocampus and its subfields in resting‐state networks - Ezama, Laura (Eur J Neurosci, 2021)
Many neuroimaging studies have shown that the hippocampus participates in a resting‐state network called the default mode network. However, how the hippocampus connects to the default mode network, whether the hippocampus connects to other resting‐state networks and how the different hippocampal subfields take part in resting‐state networks remains poorly understood. Here, we examined these issues using the high spatial‐resolution 7T resting‐state fMRI dataset from the Human Connectome Project. We used data‐driven techniques that relied on spatially‐restricted Independent Component Analysis, Dual Regression and linear mixed‐effect group‐analyses based on participant‐specific brain morphology. The results revealed two main activity hotspots inside the hippocampus. The first hotspot was located in an anterior location and was correlated with the somatomotor network. This network was subserved by co‐activity in the CA1, CA3, CA4 and Dentate Gyrus fields. In addition, there was an activity hotspot that extended from middle to posterior locations along the hippocampal long‐axis and correlated with the default mode network. This network reflected activity in the Subiculum, CA4 and Dentate Gyrus fields. These results show how different sections of the hippocampus participate in two known resting‐state networks and how these two resting‐state networks depend on different configurations of hippocampal subfield co‐activity.